Caries arrest using silver diamine fluoride: Knowledge, attitude, and perception of adult patients in Saudi Arabia - Al Hanouf Al Habdan; Amal Al Awdah; Ghaida Aldosari; Shaikha Almogbel; Rahaf Alawaji (Elsevier, 2021)
Objectives: The objective was to evaluate the current knowledge, attitude, and perception of adult patients toward SDF and identify related factors. Materials and methods: In this cross-sectional study, data were obtained from adult participants of the Kingdom of Saudi Arabia. A simple random sampling method was used. An electronic questionnaire was designed to collect data regarding participants' demographics and their knowledge, attitude, and perception toward the use of SDF. Results: The majority (86.6%) of the participants were females. Approximately 58% were ≤ 25 years of age. Overall, 77.1% of the participants had college/higher level education, and 34.2% had a monthly income of > 16000 Saudi Riyals (SAR). Approximately 75.8% of them did not suffer from medical conditions, 60.8% had tooth decay, 82.5% brushed their teeth daily, 77.7% flossed regularly, and 63% used fluoridated toothpaste. Dental pain or inflammation was reported by 87.7% of the participants (P-value < 0.001). A higher proportion of adult patients (47.8%) was strongly satisfied with the speed of treatment, 58.9% were strongly satisfied with advantages, and 24.5% were dissatisfied with disadvantages (P-value < 0.001). Disagreement (24.0%) toward SDF material use for anterior teeth was statistically high (P-value < 0.001). Females (64.5%) demonstrated strong satisfaction with the benefits of SDF material (P-value = 0.004). Participants of male sex (26.0%), education up to high school (33.0%), and income of > 16000 SAR (31.0%) showed statistically strong disagreement (P-value < 0.05) with use of SDF for anterior teeth. Conclusion: The present study demonstrates that SDF is acceptable among Saudi adults for the purpose of arresting dental caries. However, pigmentation of anterior teeth is a major concern, especially in male participants with high socioeconomic status.